Global linguistic flows : hip hop cultures, youth identities, and the politics of language - Pennycook, Alastair, 1957-; Ibrahim, Awad.; Alim, H. Samy. (New York, NY : Routledge, 2009)
"The book engages complex processes such as transnationalism, (im)migration, cultural flow, and diaspora in an effort to expand current theoretical approaches to language choice and agency, speech style and stylization, codeswitching and language mixing, crossing and sociolinguistic variation, and language use and globalization. Moving throughout the Global Hip Hop Nation, through scenes as diverse as Hong Kong's urban center, Germany's Mannheim inner-city district of Weststadt, the Brazilian favelas, the streets of Lagos and Dar es Salaam, and the hoods of the San Francisco Bay Area, this global intellectual cipha breaks new ground in the ethnographical study of langauge and popular culture."--BOOK JACKET.
Hip hop as dusty foot philosophy : engaging locality / Alastair Pennycook and Tony Mitchell -- Language and the three spheres of hip hop / Jannis Androutsopoulos -- Conversational sampling, race trafficking, and the invocation of the gueto in Brazilian hip-hop / Jennifer Roth-Gordon -- "You shouldn't be rappin', you should be skateboardin' the x-games" : the coconstruction of whiteness in an MC battle / Cecelia Cutler -- From da bomb to bomba : global hip hop nation language in Tanzania / Christina Higgins -- "So I choose to do am Naija style" : hip hop, language, and postcolonial identities / Tope Omoniyi -- "Still reppin por mi gente" : the transformative power of language mixing in Quebec hip hop / Mela Sarkar -- "Respect for da chopstick hip hop" : the politics, poetics, and pedagogy of Cantonese verbal art in Hong Kong / Angel Lin -- Dragon ash and the reinterpretation of hip hop : on the notion of rhyme in Japanese hip hop / Natsuko Tsujimura and Stuart Davis -- "That's all concept; it's nothing real" : reality and lyrical meaning in rap / Michael Newman -- Creating "an empire within an empire" : critical hip hop language pedagogies and the role of sociolinguistics / H. Samy Alim -- Takin hip hop to a whole nother level : métissage, affect, and pedagogy in a global hip hop nation / Awad Ibrahim.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Education in popular culture; Language and culture; Intercultural communication; Group identity; Hip-hop -- Influence; Culture and globalization; Electronic books